Benchmarking der Infrastruktur von Schweizer Privatbahnen. - (:unkn) unknown (My University, 2004)
The principal top class roads in use - or projected according to long term plans for the Canton of Zurich - were originally devised in the sixties and seventies. Known bottlenecks, coupled with anticipated instances of traffic flows regularly taxing the existing facilities, allow strategies to be developed for future road network expansion. The strategy at hand for top class roads, forms part of an overall transport scheme for the Canton of Zurich. difu
Keywords: Öffentlicher Verkehr; Eisenbahn; Privatisierung; Verkehrsinfrastruktur; Privatbahn; Benchmarking